Willingness To Pay Petani terhadap Pelaksanaan Asuransi Usaha Tani Padi (AUTP) (Studi Kasus Subak Cepik Desa Tajen Kecamatan Penebel Kabupaten Tabanan) - SURNING, NI NENGAH; AMBARAWATI, I GUSTI AGUNG AYU; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018, 2018)
Farmer’s Willingness to Pay to the Implementation of Rice Farming Insurance (Case Study of Subak Cepik Tajen Village, District of Penebel Tabanan Regency) Asuransi Usaha Tani Padi (AUTP) is one of program by Indonesia Government to protect the farmers if there is a risk happen and causes the farmer loss their results during paddy farming. Subak Cepik is one of subak join AUTP since 2015 and having the most claims in Bali Province. The purpose of this research is to find out about willingness to pay by the farmers or we can understanding it as farmer’s ability to pay premiums AUTP and to know the constraints that occurs in the implementation of AUTP for the Subak Cepik farmers and PT Jasindo. This research is using descriptive quantitative and descriptive qualitative method and used 40 sample of farmers. The data analyzed using Contingent Valuation Method (CVM). The result of this research shows that farmer’s willingness to pay is Rp 30,853/ha/planting season. The amount is smaller than the current premium of Rp 36,000/ha/planting season.. Besides, this research also shows obstacles in the implementation of AUTP for farmers that is from the process of socialization AUTP, premium payment process and claims fund that is still lack for farming needs and constraints from the PT Jasindo including the process of socialization and registration process of AUTP participants. Subak Cepik farmers still want government subsidies and want to improve the service of AUTP. Result from this research suggest there is a need to synergize PT Jasindo and the farmers need for synergy. Then, the government also expected to set the AUTP premium in accordance with the capability of farmers.